International Patent Law Conflicts With the Right of Access to Medicines and Healthcare: Key Aspects - Simonyan, Ani (Bulletin of Yerevan University C: Jurisprudence, 2023)
This article is dedicated to the legal conflicts between international patent law and the right ofaccess to medicines and healthcare. This article discusses the problem above under the light ofthe framework of the international agreements, mainly WTO Agreement on Trade-RelatedAspects of Intellectual Property Rights (TRIPS Agreement) and Doha Declaration on the TRIPSagreement and public health. As we know, patents give exclusive rights to the inventors to usetheir innovations for a long period of time. This limits the ability of public to get easy access tomedications, consequently to indispensable healthcare. It is undoubtable that the quality of lifeand the healthcare of the public is an absolute priority. On the contrary, the expropriation ofpatent rights, inadequate compensation of damages for issuing the compulsory licensing mayhave irreversible consequences for the states. Foreign investor may file claims against thegovernmental authorities to ad hoc or permanent arbitral institutions.
Keywords: access to medicines; public health; TRIPS agreement; pharmaceutical patent disputes; Doha Declaration; compulsory licensing; foreign investment; patent law